Quality management: A basic instrument in healthcare systems - Hans-Günther Sonntag (Биомедицинска истраживања, 2021)
In industry and the public sector quality has become the important management challenge of the 21st century. Although quality should be self-understanding in healthcare the reality shows another picture. There are nowadays international standards and models of quality excellence which make the introduction and control of quality management even in healthcare easier and allow a better benchmarking. The Model of Business Excellence of the EFQM with the five enabler criteria and the four result criteria can be used as a basic guideline. Focusing on such main parameters like leadership, people, strategy and policy, resources and processes which are important background criteria for quality it can be easily adapted to the requests of quality in almost all healthcare fields. Definitions of the different quality aspects like quality assurance, quality management, total quality management, quality control show that there are still special quality parameters in healthcare which need to be recognized. Reality in healthcare still shows a lot of deficiencies concerning quality measurements. Quality in healthcare including the mentioned key criteria will only be effective if it is an integrated part of the daily work by all people who are concerned with healthcare.
Keywords: Quality management in healthcare; quality control; EFQM; Model of Business Excellence; DIN EN ISO 9001